Respostas
respondido por:
0
11(×+12)-410=2(×-4)+89
11x + 132 - 410 = 2x -8 + 89
11x -2x = -8 +89 +410 -132
9x = 359
x = 39,88
11x + 132 - 410 = 2x -8 + 89
11x -2x = -8 +89 +410 -132
9x = 359
x = 39,88
respondido por:
0
11(x + 12) - 410 = 2(x - 4) + 89
11x + 132 - 410 = 2x - 8 + 89
11x - 2x = - 8 + 89 - 132 + 410
9x = 359
x = 359/9
S = { 359/9 }
11x + 132 - 410 = 2x - 8 + 89
11x - 2x = - 8 + 89 - 132 + 410
9x = 359
x = 359/9
S = { 359/9 }
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás